Ð˜ÑÐ¿Ð¾Ð»ÑŒÐ·Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð¼ÐµÑ‚Ð¸Ð»Ñ†ÐµÐ»Ð»ÑŽÐ»Ð¾Ð·Ñ‹ Ð¿Ñ€Ð¸ ÐºÑƒÐ»ÑŒÑ‚Ð¸Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ð¸ Ð¸ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ð¸ Ð¿ÐµÑ€ÐµÐ²Ð¸Ð²Ð°ÐµÐ¼Ð¾Ð¹ ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€Ñ‹ Ð¡ÐŸÐÐ’ - Koshchiy, S. V.; Vysekantsev, I. P.; Martsenyuk, V. F.; Petrenko, T. F.; Kudokotseva, E. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The possibility of adaptation of cultured embryonic pig kidney cells (SPEV) to growth in culturing medium 199+0.1% MC with reduced serum content to 1% has been shown. Cryoprotective properties of MC for the cryopreservation of SPEV have been determined.